Pengembangan Media Digital Interaktif dan Permainan Ulartangga pada Materi Hobi dan Perbedaan untuk Siswa Kelas 2 Sekolah Dasar - Sasikirani, Nadia (Journal of Contemporary Issues in Primary Education, 2025)
This development research aims to produce an interactive media named “Aku dan Teman-Temanku” (Me and My Friends) based on digital multimedia integrated with the Snakes and Ladders game. It also aims to test its feasibility, practicality, and effectiveness in enhancing the understanding of second-grade elementary school students. The main problem addressed is the low level of student engagement and difficulty in comprehending thematic material due to conventional learning methods. This study uses the Research and Development (R&D) model with the ADDIE stages (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, expert validation, student response questionnaires, and pretest and posttest. The expert validation results showed that the media was in the Very Feasible category (average 90%), and the field trials showed the Very Good category (average 92.6%) for practicality.The effectiveness of the media was proven to be significant, demonstrated by an increase in the average learning outcome score from 63 to 87 (a 24-point increase) and a drastic rise in classical mastery from 48% to 91% (a 43% increase). Thus, this interactive media is proven effective as an innovative solution to create an engaging, interactive learning experience that successfully increases the understanding of social material among low-grade students.